Effects of Testosterone and Evoked Resistance Exercise after Spinal Cord Injury (TEREX-SCI): study protocol for a randomised controlled trial. Issue 4 (4th April 2017) - Gorgey, Ashraf S; Khalil, Refka E; Gill, Ranjodh; O'Brien, Laura C; Lavis, Timothy; Castillo, Teodoro; Cifu, David X; Savas, Jeannie; Khan, Rehan; Cardozo, Christopher; Lesnefsky, Edward J; Gater, David R; et al.
Abstract : Introduction: Individuals with spinal cord injury (SCI) are at a lifelong risk of obesity and chronic metabolic disorders including insulin resistance and dyslipidemia. Within a few weeks of injury, there is a significant decline in whole body fat-free mass, particularly lower extremity skeletal muscle mass, and subsequent increase in fat mass (FM). This is accompanied by a decrease in anabolic hormones including testosterone. Testosterone replacement therapy (TRT) has been shown to increase skeletal muscle mass and improve metabolic profile. Additionally, resistance training (RT) has been shown to increase lean mass and reduce metabolic disturbances in SCI and other clinical populations. Methods and analysis: 26 individuals with chronic, motor complete SCI between 18 and 50 years old were randomly assigned to a RT+TRT group (n=13) or a TRT group (n=13). 22 participants completed the initial 16-week training phase of the study and 4 participants withdrew. 12 participants of the 22 completed 16 weeks of detraining. The TRT was provided via transdermal testosterone patches (4–6 mg/day). The RT+TRT group had 16 weeks of supervised unilateral progressive RT using surface neuromuscular electrical stimulation with ankle weights. This study will investigate the effects of evoked RT+TRT or TRT alone on body composition (muscle cross-sectional area, visceral adipose tissue, %FM) and metabolic profile (glucose and lipid metabolism) in individuals with motor complete SCI. Findings from this study may help in designing exercise therapies to alleviate the deterioration in body composition after SCI and decrease the incidence of metabolic disorders in this clinical population. Ethics and dissemination: The study is currently approved by the McGuire VA Medical Center and Virginia Commonwealth University. All participants read and signed approved consent forms. Results will be submitted to peer-reviewed journals and presented at national and international conferences. Trial registration number: Pre-result, NCT01652040 .